Melliferous flora of the central-eastern region of the municipality of Pátzcuaro, Michoacán, Mexico - Araujo-Mondragón, Fernando; Redonda-Martínez, Rosario (Instituto de Ecología, A.C., 2019)
Background and Aims: Honey plants are those that mainly produce nectar and pollen, although those that generate propolis are also considered in this category. The beekeepers, before installing an apiary, need to know the honey flora of a region, because the honey production depends on it. The objective of this work was to identify the honey plants that grow in the central-eastern region of the municipality of Pátzcuaro, Michoacán, Mexico.Methods: Field work was carried out in areas close to four reference apiaries, in a radius of one kilometer, using as a reference point each of the apiaries located in the central-eastern region of the municipality of Pátzcuaro. Feeding preferences and pollen collection of Apis melliferawere observed, specimens of the plants that it uses were collected, and its visits were documented by photographs. Finally, honey samples were taken in two seasons of the year, one before the flowering peak of the honey species in the area and another in the honey harvest season, with the purpose of performing melisopalynological studies to identify pollen types present in the honey.Key results: Ninety-three species of honey plants, belonging to 33 botanical families, were identified; Asteraceae was the most representative. In the melisopalinological analyses an average of 16 pollen types per sample was observed; the Asteraceae pollen was the most abundant.Conclusions: The honey flora of the studied region has been affected by its eradication, because most of the species are weeds, due to the change in land use to install mainly avocado orchards, and the grasshoppers pests that defoliate the plants, causing delay or absence of flowering.